Penguatan Daya Saing UMKM Agroindustri Singkong Melalui Implementasi Inovasi Kemasan Ramah Lingkungan dan Pemberdayaan Masyarakat - Widowati, Fika Ulfa (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the cassava agro-industry have strategic potential to support the rural economy, but face challenges in product competitiveness and environmental sustainability. This research aims to enhance the competitiveness of cassava agro-industry MSMEs thru eco-friendly packaging innovation and community empowerment. The method uses a participatory approach with the stages of socialization, training, mentoring, and evaluation. The program was implemented in Kaliwungu District, Kendal Regency, over a period of 6 months, involving 25 MSMEs. The results show an average increase in turnover of 35% and a substantial improvement in packaging quality. Environmental impacts include an 80% reduction in plastic thru cassava flour and recycled paper packaging, and a 65% decrease in packaging waste. Measurable social impacts include: increasing the capacity of 120 family members in digital business (85% able to operate e-commerce), forming 5 joint business groups, creating 15 new jobs, and improving financial literacy (78% able to prepare simple financial statements). The program creates a multiplier effect by increasing the adoption of digital technology from 20% to 85%. Evaluation shows sustainability thru a system of local partnerships and an integrated distribution network. This research contributes to the development of a green innovation-based MSME empowerment model that can be replicated in other agro-industrial regions, supporting the achievement of SDGs goals 8, 12, and 17.